Effect of Ayurveda Formulation in the Management of Secondary Infertility with Uterine Fibroid (AYUSHDHARA, 2025)
In Ayurveda, infertility or Vandhyatva, is viewed as a complication of Yoni Vyapad (gynecological disorders) and is also associated with Artavavaha Srotodushti Lakshana, indicating a disruption in the channels responsible for menstrual and reproductive functions. A 32 year old lady complaining of inability to conceive a viable child with associated complaint of pain in lower abdomen, thick white discharge P/V, backache, constipation, loss of appetite. On USG, she was diagnosed with intra mural fibroid (19mm×18mm) over posterior wall. Her HSG was normal, A comprehensive Ayurvedic treatment plan was administered, which included Raktashodhaka (blood purification) and Lekhana (scraping or dissolving) therapies, along with Yoga Basti in two cycles. Additionally, emphasis was placed on Nidana Parivarjana (avoiding the causative factors) and Beejsanskara (genetic purification or cleansing). The regimen was complemented with Rajaswalacharya (guidelines for menstruation) to support overall well-being. She was also provided with Sthanika Karmas (localized treatments), including Yonidhawana and Yonipichu, to support localized healing and enhance the effectiveness of the overall treatment plan. Treatment was continued for one year 2 months with a follow up once in 15 days and relief in all symptoms, she conceived and coming for regularly ANC check-up her POG- 35weeks continued antenatal period is going uneventful.